2022
DOI: 10.1093/plphys/kiac423
|View full text |Cite
|
Sign up to set email alerts
|

Dual-function DEFENSIN 8 mediates phloem cadmium unloading and accumulation in rice grains

Abstract: Grain cadmium (Cd) is translocated from source to sink tissues exclusively via phloem, though the phloem Cd unloading transporter has not been identified yet. Here, we isolated and functionally characterized a defensin-like gene DEFENSIN 8 (DEF8) highly expressed in rice (Oryza sativa) grains and induced by Cd exposure in seedling roots. Histochemical analysis and subcellular localization detected DEF8 expression preferentially in pericycle cells and phloem of seedling roots, as well as in phloem of grain vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Plant defensins, such as CAL1 and DEF8, also mediate the long-distance transport of defensin–Cd complexes in rice plants. , However, it remains unclear how Cd is detached from defensin–Cd complexes and re-chelated by extracellular defensins after export into the apoplastic space. Because OsThi9 has a signal peptide, Cd-binding activity, and is localized to the cell walls as a mature protein, we hypothesize that this protein promotes Cd efflux from the cytoplasm to the apoplasm via chelation and signal peptide-mediated secretion, similar to CAL1 or DEF8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant defensins, such as CAL1 and DEF8, also mediate the long-distance transport of defensin–Cd complexes in rice plants. , However, it remains unclear how Cd is detached from defensin–Cd complexes and re-chelated by extracellular defensins after export into the apoplastic space. Because OsThi9 has a signal peptide, Cd-binding activity, and is localized to the cell walls as a mature protein, we hypothesize that this protein promotes Cd efflux from the cytoplasm to the apoplasm via chelation and signal peptide-mediated secretion, similar to CAL1 or DEF8.…”
Section: Discussionmentioning
confidence: 99%
“…halleri . Recently, plant defensins in Arabidopsis and rice have also been shown to play a role in the mitigation of heavy-metal (Cd) toxicity and accumulation. ,,, …”
Section: Discussionmentioning
confidence: 99%
“…Gu et al isolated DEFENSIN 8 (DEF8), a defensin-like gene expressed in rice grains, and suggested that DEF8 promotes Cd loading into the xylem and mediates Cd translocation from root to shoot and subsequent distribution in the grain [97]. DEF8 is also a modulator of Cd unloading to the phloem without affecting the accumulation of essential mineral nutrients and key crop traits [98].…”
Section: Hm Tolerant Transgenic Ricementioning
confidence: 99%
“…In this issue of the Plant Physiology , Tian-Yu Gu and colleagues ( Gu et al 2022 ) demonstrate the role of defensin family member DEF8 as a mediator of xylem Cd loading and phloem Cd unloading in rice. Defensins are a group of cysteine-rich proteins composed of the cysteine-rich domain that can bind to metal ions and the secretion signal peptide (SSP).…”
mentioning
confidence: 99%
“…DEF8–Cd indicates a hypothetical complex of Cd and DEF8. The figure is based on Figure 8 from Gu et al (2022) .…”
mentioning
confidence: 99%